Non-data-aided carrier offset estimators for OFDM with null subcarriers: identifiability, algorithms, and performance - Xiaoli Ma; Tepedelenlioglu, C.; Giannakis, G.B.; Barbarossa, S. (IEEE journal on selected areas in communications, 2001)
The ability of orthogonal frequency-division multiplexing systems to mitigate frequency-selective channels is impaired by the presence of carrier frequency offsets (CFOs). In this paper, we investigate identifiability issues involving high-resolution techniques that have been proposed for blind CFO estimation based on null subcarriers. We propose new approaches that do not suffer from the lack of identifiability and adopt adaptive algorithms that are computationally feasible. The performance of these techniques in relation to the location of the null subcarriers is also investigated via computer simulations and compared with the modified Cramer-Rao bound.